The cardioprotective properties of Persicaria maculosa and Citrus sinensis extracts against doxorubicin-induced cardiotoxicity in mice - Mohammad Zaki; Ibrahim Helmi El-Sayed; Mamdouh Abdel-Mogib; Ashraf El-Shehawy; Omali El-Khawaga (Mashhad University of Medical Sciences, 2024)
Objective: This study assessed the cardioprotective properties ofPersicaria maculosa (PME) and Citrus sinensis (CME) hydromethanolic extracts, besides Citrus sinensis aqueous extract(CWE) against doxorubicin (DOX)-induced cardiotoxicity.Materials and Methods: The extracts were characterized. Micewere divided into eight groups: control (saline), DOX, protected(injected with 200 mg/kg of PME, CWE or CME for 21 days,orally, and DOX), and extracts (PME, CWE or CMEadministration, orally, for 21 days). DOX was injected (5 mg/kg,ip) on days 8, 13 and 18 of the experiment. Cardiac tumor necrosisfactor-alpha (TNF-α), nuclear factor (erythroid-derived 2)-like 2(Nrf2) and carbonyl reductase 1 (CBR1) expression levels, besidessuperoxide dismutase, catalase, malondialdehyde, nitric oxide andtotal protein levels were evaluated. Serum lactate dehydrogenase,creatine phosphokinase cardiac isoenzyme, aspartate transaminase,cholesterol, triglycerides and creatinine levels, as well as thecardiac tissues were examined.Results: Comparing with the control, DOX considerably (p<0.01)up-regulated TNF-α expression, malondialdehyde, nitric oxide,cardiac enzymes, lipids and creatinine levels, while it significantly(p<0.01) down-regulated Nrf2 and CBR1. Additionally, DOXinterfered with antioxidant enzymes' activities (p<0.01).Conversely, protected groups showed a significant (p<0.01)amelioration of DOX-induced cardiotoxic effects.Conclusion: The current study provides a new understanding of P.maculosa and C. sinensis cardioprotective mechanisms. Theextracts' cardioprotective effects may be due to their antioxidantactivities, ability to maintain the redox homeostasis throughregulation of important antioxidant genes and primary antioxidantenzymes, and capability to recover inflammatory cytokines andlipids levels. Noteworthy, the tested extracts showed no toxicchanges on the normal mice.